Cell-bound lipases from Burkholderia sp. ZYB002: gene sequence analysis, expression, enzymatic characterization, and 3D structural model. Issue 1 (December 2016) - Shu, Zhengyu; Lin, Hong; Shi, Shaolei; Mu, Xiangduo; Liu, Yanru; Huang, Jianzhong
Abstract Background The whole-cell lipase fromBurkholderia cepacia has been used as a biocatalyst in organic synthesis. However, there is no report in the literature on the component or the gene sequence of the cell-bound lipase from this species. Qualitative analysis of the cell-bound lipase would help to illuminate the regulation mechanism of gene expression and further improve the yield of the cell-bound lipase by gene engineering. Results Three predictive cell-bound lipases, lipA, lipC21 andlipC24, fromBurkholderia sp. ZYB002 were cloned and expressed inE. coli . Both LipA and LipC24 displayed the lipase activity. LipC24 was a novel mesophilic enzyme and displayed preference for medium-chain-length acyl groups (C10-C14). The 3D structural model of LipC24 revealed the open Y-type active site. LipA displayed 96 % amino acid sequence identity with the known extracellular lipase.lipA -inactivation andlipC24 -inactivation decreased the total cell-bound lipase activity ofBurkholderia sp. ZYB002 by 42 % and 14 %, respectively. Conclusions The cell-bound lipase activity fromBurkholderia sp. ZYB002 originated from a multi-enzyme mixture with LipA as the main component. LipC24 was a novel lipase and displayed different enzymatic characteristics and structural model with LipA. Besides LipA and LipC24, other type of the cell-bound lipases (or esterases) should exist.